Development of Student Worksheet by using Discovery Learning Approach for Senior High School Student - I Made Astra; Hadi Nasbey; Nur Devia Muharramah (TARBIYA: Journal of Education in Muslim Society, 2015)
Abstract The aim of this research is to create student worksheet for physics learning  by using discovery learning approach as a learning material referring to curriculum 2013. The method used in this research is research and development. This research consists of five steps: 1) needs analysis, 2) product development, 3) Validation by expert, 4) field test in small scale, and 5) field test in large scale. The average score for student worksheet are 92% from concept expert, 79,56% from media expert, and 91,51% from physics teacher. After revised, the student worksheet was evaluated by a field test in a small and large scale. The average score from both scale are 70,66% and 75,08 respectively. It is conluded that student worksheet by using discovery learning approach can be used and distributed as a learning material in physics learning for senior high school student grade X Abstrak Penelitian pengembangan ini  bertujuan untuk menghasilkan produk berupa Lembar Kegiatan Siswa (LKS) pembelajaran fisika SMA dengan pendekatan Discovery Learning sebagai bahan ajar yang mengacu pada kurikulum 2013 pada Kompetensi Dasar praktikum kelas X semester genap. Metode yang digunakan pada penelitian ini adalah penelitian dan pengembangan. Prosedur penelitian dan pengembangan ini terdiri dari lima tahap, yaitu: 1) analisis kebutuhan, 2) pengembangan produk, 3) validasi ahli, 4) uji coba lapangan skala kecil, dan 5) uji coba lapangan skala besar. LKS fisika dengan pendekatan Discovery Learning telah melalui tahap uji validasi dengan presentase pencapaian sebesar 92%, menurut ahli materi, 79,56% menurut validasi ahli media, dan 91,51 % menurut guru fisika SMA. Setelah di revisi, LKS di uji cobakan skala kecil kepada 5 siswa menunjukan persentase capaian  sebesar  70,66%  dan  uji  lapangan  menunjukan persentase capaian  sebesar 75,08%. Dari penelitian ini,  dapat disimpulkan bahwa  LKS  dengan pendekatan Discovery Learning  yang dikembangkan sudah layak untuk digunakan dan disebarluaskan sebagai bahan ajar fisika kelas X semester genap How to Cite:  Astra, I. M., Nasbey, H., Muharramah, N. D., (2015). Development of Student Worksheet by Using Discovery Learning Approach for Senior High School Student. TARBIYA: Journal Of Education In Muslim Society, 2(1), 91-96. doi:10.15408/tjems.v2i1.1749. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1749